Development of a Digital Tourism Model Using Virtual Reality as Sociological Restoration at the Foot of Mount Sinabung - Hasibuan, Annalisa Sonaria; Destiadi, Rezha; Fajrin, Alfannisa Annurrallah; Pinem, Kynta Bretyna (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Mount Sinabung is an active volcano located in the Karo Highlands, specifically in the Karo Regency of North Sumatra, Indonesia. Sinabung and Mount Sibayak, located in North Sumatra, are both active volcanoes and rank as the second-highest peaks in the province. However, it saw a dramatic resurgence and became active once more with a volcanic eruption on August 27, 2010. The most recent eruption of this mountain took place on February 19, 2018 and is ongoing. The significance of this situation prompted the study team to engage in the development of an empowerment paradigm. The objective of this study is to create a digital tourism framework for communities impacted by the eruption of Mount Sinabung, utilizing virtual reality technology as a means to facilitate societal repair. The research methodology employed is a hybrid approach. The data results are processed and evaluated using a customized technique that takes into account the specific demands of the community and parties involved in the collaborative model development. This analysis is done both qualitatively and quantitatively. The analytical stage of discussing the desired digital tourist model employs the theory of viewing techniques, which is akin to reading, in the form of the selection stage.